2015
DOI: 10.1177/1756287215617872
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation therapy and cardiovascular disease: what is the linking mechanism?

Abstract: Abstract:The past decade has brought increased awareness of the potential adverse effects of androgen deprivation therapy (ADT) in men with prostate cancer. Arguably the most important and controversial of these is the increased risk of cardiovascular morbidity and mortality. Although multiple observational studies have shown that men treated with ADT are at increased risk of developing atherosclerotic cardiovascular disease, our understanding of the biological mechanisms that might underlie this phenomenon is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 94 publications
2
49
0
Order By: Relevance
“…22,23 The pathogenesis of HF is characterized by progression from cardiovascular risk factors and cardiac injury toward the development of cardiomyopathy and clinical symptoms in which neurohormonal factors and cardiometabolic milieu have an important role. 24 Studies have shown that testosterone receptors in cardiomyocytes can induce the release of intracellular calcium in cardiomyocytes and, as a result, testosterone deficiency can lower the contractile function of the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The pathogenesis of HF is characterized by progression from cardiovascular risk factors and cardiac injury toward the development of cardiomyopathy and clinical symptoms in which neurohormonal factors and cardiometabolic milieu have an important role. 24 Studies have shown that testosterone receptors in cardiomyocytes can induce the release of intracellular calcium in cardiomyocytes and, as a result, testosterone deficiency can lower the contractile function of the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…65 A retrospective analysis, however, using data from the Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) and including men with prostate cancer treated with radical prostatectomy followed or not with ADT found a significant correlation of ADT with increased CV mortality, but only among patients over 65 years old (p=0.002). 66 Furthermore, a recent meta-analysis of randomized controlled trials and observational studies showed that antiandrogen was associated with a 30% decreased risk for myocardial infarction compared to GnRH agonists, while combined androgen blockade was associated with a 10% increased risk for stroke when compared to antiandrogen. 67 In the Radiation Therapy Oncology Group (RTOG) study protocol 85-31, 68 patients with advanced prostate cancer who had either radiotherapy alone or in combination with indefinite ADT were enrolled and demonstrated no statistically significant difference regarding mortality related to CVD between the two groups (p=0.17).…”
Section: Adt and The Risk Of Cardiovascular Diseasementioning
confidence: 99%
“…[2][3][4] The risk of developing metabolic syndrome remains elevated even with intermittent ADT-14.7% at 12 months-but is lower than that indicated by studies on continuous ADT. 11 ADT AND HYPERTENSION Low levels of testosterone have been associated with decreased arterial compliance, 4 GnRH agonists and antagonists have been demonstrated to increase arterial stiffness, 20 and insulin resistance has been suggested to blunt the regulation of vascular tone. 18 However, only the new hormonal agents, abiraterone and enzalutamide, have demonstrated consistent association with hypertension.…”
Section: Adt Insulin Resistance and Diabetes Mellitusmentioning
confidence: 99%
“…3,6 Implicated mechanisms that underlie the metabolic and atherothrombotic changes of ADT include the loss of androgenmediated inhibition of stem-cell differentiation into adipocytes and free fatty acid mobilization into triglycerides, a decrease in lipolysis, and compromised reverse cholesterol transport from the arteries to the liver. 20 Elevated levels of cytokines, adiponectin, and fibrinogen create an inflammatory milieu that may contribute to both insulin resistance and atherogenesis. 3,4 Cells that express GnRH receptors are susceptible to GnRH agonist-mediated effects, such as T-cell activation with a subsequent disruption of androgen-mediated modulation of inflammatory responses.…”
Section: Adt Insulin Resistance and Diabetes Mellitusmentioning
confidence: 99%